Development of a new method for assessing the heart rate increase during tests in human carrying centrifuge - Zawadzka-Bartczak, Ewelina; Kopka, Lech; Kowalczuk, Krzysztof; Krej, Mariusz (Polski merkuriusz lekarski, 2020)
Exposition to head to foot accelerations (+Gz) on human carrying centrifuge are associated with increase in heart rate (HR). Sometimes, especially with extremely high HR values it is almost impossible to distinguish between fast sinus rhythm and supraventricular tachycardia which is essential for the safety of the subject and therefore the decision regarding break the centrifuge examination earlier. The aim of the work was to answer the question: what is the maximum physiological rise of the sinus heart rate, recorded beat to beat, during tests in the overload centrifuge, which should lead to the suspicion of paroxysmal supraventricular tachycardia? The material tested was an electrocardiogram (ECG) digital records of 150 pilots, achieved during both GOR and ROR tests, carried out in the human centrifuge. The HR, increase of HR (ΔHR) and their changes accompanying the + Gz acceleration ware analysed. Mean values of the parameters determined from all centrifuge exposures were: HR - 105.8 beats per minutes (bpm,) ΔHR 2.5, + Gz 4.06. There was no relationship between ΔHR and + Gz increase The values of ΔHR, meeting the eligibility criteria for the possible PT, were in the range 2.41 to 11.19 bpm on average 2.5 bpm. Rapid/unexpected HR beat to beat acceleration (ΔHR) during a GOR or ROR centrifugal test, exceeding 11 beats/min, in relation to the HR rate immediately preceding it and persisting for at least 4 consecutive heart evolutions, requires the attention of the examining doctor, and ECG should be examined for paroxysmal tachycardia.